Comparative Cytotoxicity Evaluation of Heat-Assisted vs Cold Water Extractions of Six Medicinal Fungi against Breast and Lung Cancer Cells - Ng, Min-Jia; Goh, Neng-Yao; Tan, Chon-Seng; Razif, Muhammad Fazril Mohamad; Yap, Hui-Yeng Yeannie; Kong, Boon-Hong; Fung, Shin-Yee (Food technology and biotechnology, 2024)
Research background. Preparation of medicinal fungi for experimental purposes usually involves the extraction and determination of the quality and quantity of bioactive compounds prior to the biological experiment. Water, a common polar solvent, is usually used for traditional preparations for consumption. The application of high temperatures during water extraction can affect the chemical composition and functional properties of the extracts. Therefore, the aim of this study is to compare the differences in composition between extracts obtained with heat-assisted and cold water extractions of six selected species of fungi (Lignosus rhinocerus, Ophiocordyceps sinensis, Inonotus obliquus, Antrodia camphorata, Phellinus linteus and Monascus purpureus) and their cytotoxicity against human lung and breast cancer cells. Experimental approach. The extracts obtained with heat-assisted and cold water extraction of six species of fungi were analysed to determine their protein, carbohydrate and phenolic contents. Their cytotoxicity was tested against lung (A549) and breast (MCF-7 and MDA-MB-231) cancer cell lines. The most potent extract was further separated into its protein and non-protein fractions to determine their respective cytotoxicity. Results and conclusions. The cytotoxicity of the different extracts obtained with heat-assisted and cold water extraction varied. Comparing the two extractions, the cold water extraction resulted in a significantly higher yield of proteins (except M. purpureus) and phenolic compounds (except A. camphorata), while the extracts of I. obliquus and M. purpureus obtained with heat-assisted extraction had a significantly higher carbohydrate mass fraction. Notably, the cold water extract of I. obliquus showed cytotoxicity (IC50=(701±35) μg/mL), which was one of the highest of the extracts tested against A549 cells. The cold water extract of I. obliquus was selected for further studies. Our results showed that cold water extracts generally have higher cytotoxicity against selected human cancer cell lines, with the exception of O. sinensis and A. camphorata extracts. Novelty and scientific contribution. This study reports the advantage of cold water extracts of fungi over those obtained with heat-assisted extraction in terms of cytotoxicity against human cancer cell lines and emphasises the role of extraction conditions, particularly heat, in influencing chemical composition and cytotoxic effects.